Scribal culture in ancient Egypt - Allon, Niv ca. 20./21. Jh; Navratilová, Hana 1979- (Cambridge elements, 2023)
This Element seeks to characterize the scribal culture in ancient Egypt through its textual acts, which were of prime importance in this culture: writing, list-making, drawing, and copying. Drawing upon texts, material objects, and archeological evidence, this Element will touch upon main themes at the heart of the study of this culture, while building on current discussions in literacy and literary as well as social history